2009
DOI: 10.1073/pnas.0904021106
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinia virus inoculation in sites of allergic skin inflammation elicits a vigorous cutaneous IL-17 response

Abstract: Eczema vaccinatum (EV) is a complication of smallpox vaccination occurring in patients with atopic dermatitis. In affected individuals, vaccinia virus (VV) spreads through the skin, resulting in large primary lesions and satellite lesions, and infects internal organs. BALB/c mice inoculated with VV at sites of Th2-biased allergic skin inflammation elicited by epicutaneous ovalbumin (OVA) sensitization exhibited larger primary lesions that were erosive, more satellite lesions, and higher viral loads in skin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
54
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(70 citation statements)
references
References 27 publications
16
54
0
Order By: Relevance
“…Two reports suggest that Th17 cells exacerbate dermatitis because increased numbers of Th17 cells were found in the peripheral blood and acute lesional skin of AD patients (31). Kawakami et al (32) also support this idea with their study of NK cell function in AD patients (23). In contrast, two reports suggest that low IL-17 expression or reduced responses to IL-17 in the skin cause AD-like symptoms (24,33).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Two reports suggest that Th17 cells exacerbate dermatitis because increased numbers of Th17 cells were found in the peripheral blood and acute lesional skin of AD patients (31). Kawakami et al (32) also support this idea with their study of NK cell function in AD patients (23). In contrast, two reports suggest that low IL-17 expression or reduced responses to IL-17 in the skin cause AD-like symptoms (24,33).…”
Section: Discussionsupporting
confidence: 51%
“…Proteins (5 mg) were fractionated by 10% SDS-PAGE and transferred onto a Hybond-P polyvinylidene difluoride membrane (GE Healthcare, Buckinghamshire, U.K.). A rabbit polyclonal Ab raised against TRAF3IP2 (anti-Act1 [H-300]) was obtained commercially (Santa Cruz Biotechnology, Santa Cruz, CA) and has been characterized previously (23,24). The Ab was used at a dilution of 1:400.…”
Section: Western Blottingmentioning
confidence: 99%
“…Hou et al [23] reported that Th17 cells promote persistent viral infection in a model of chronic virus infection and IL-17 upregulates anti-apoptotic molecules and consequently increases persistent infection by enhancing the survival of virus-infected cells and blocking target cell destruction by cytotoxic T cells. Also, Oyoshi et al [24] reported that IL-17 contributes to viral replication in a model of disseminated vaccinia infection rather than providing host defense against viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…Virus inoculation at sites of experimentally induced Th2-biased allergic skin inflammation resulted in more severe lesions, higher viral DNA loads in the skin and internal organs and more satellite lesions when compared to inoculation on unsensitized skin [36]. Local expression of IL-17 and ineffective T cell responses may also be involved in the susceptibility of patients with AD to EV [36,37,38]. …”
Section: Discussionmentioning
confidence: 99%
“…A number of animal models of EV have been explored by others to understand the biological and molecular basis for the potentially life-threatening VV dissemination which can be seen in some individuals after vaccination against smallpox [36,37,38]. Virus inoculation at sites of experimentally induced Th2-biased allergic skin inflammation resulted in more severe lesions, higher viral DNA loads in the skin and internal organs and more satellite lesions when compared to inoculation on unsensitized skin [36].…”
Section: Discussionmentioning
confidence: 99%